Gestão da informação: do fluxo informacional aos processos de compartilhamento no setor de provimento da Universidade Federal da Paraíba - Souza, Laurivania Daniella Silva de (2020)
This work aimed to investigate how the information sharing processes occur in the Division of Selection and Provision of the Dean of Personnel Management at the Federal University of Paraíba. The relevance of the studied topic consists in the fact that information is currently considered an essential economic resource for organizations. This time, information sharing has become a strategic advantage, as it keeps the organizational memory alive. The research had a qualitative and quantitative approach, characterized as exploratory, applied and descriptive research, as well as using bibliographic, documentary research and the application of an electronic questionnaire for data collection. For the analysis of the categories, the analysis model proposed by Choo (2003) was used. The survey and analysis of the data during the research made it possible to analyze how information sharing occurs primarily within the Division of Selection and Provision of the Dean of Personnel Management at the Federal University of Paraíba. The results found confirmed what other research carried out in this area of sharing highlights. The data reveal that the actors face barriers regarding sharing. Among the listed barriers, the lack of tools to assist in sharing is highlighted. According to the survey, the main means used by respondents to share is face to face. The research enabled the creation of a tool to improve the sharing of information with in. The final product of the research was the construction of an infographic to be used as a model for sharing in formation with in the researched division.